The influence of travel motivations and social factors on travel web site usage among Malaysian travellers - Abd Aziz, N.; Musa, G.; Sulaiman, A. (2010)
In this study the framework is developed based on the theory of reasoned action. This paper seeks to examine the influences of travel motivations and social factors on future intention to use travel web sites. Data was collected using multistage cluster sampling among employees in selected organisations in the Klang Valley of Malaysia. A total of 679 questionnaires were returned and analysed. The results showed that the travel motivation of entertainment and sports activities have positive influences on hedonicbased future intention to use travel web sites. On the other hand, travel motivation of familiar destination has negative influences on the similar criterion. The social factor of human interaction was not only more important than media exposure but also the strongest predictor of both hedonicbased and utilitarian-based future intention to use travel web sites. Based on these findings, the paper highlights its theoretical, marketing and managerial contributions.